Study The Temperature Distribution Of Solar Powered Drying Chamber Using CFD Simulation - Shaikh Ahmad Hilmy, Shaikh Tahfiq Falahin (2021)
Solar drying technique had been around from the beginning of civilization and continue to be used up to these days. Throughout the years, the development of new technology seen the wide varieties of solar drying techniques. The most basic being the open drying technique which used up a lot of spaces and slow drying process. The invention of solar dryer marks the development in the solar drying techniques. The solar dryer can be classifies as passive, active and hybrid solar dryer. Throughout the years, development of solar dryer has taken a significance advancement. The use of software such as ANSYS and Matlab is a common practice to designed a solar dryer nowadays. This paper focused on the use of ANSYS software to simulate the solar dryer operation and study the temperature distribution of three design of solar dryer. The design consist of solar dryer with no reflector, 45° reflector and 60° reflector. The drawing of the solar dryer was done using DesignModeler then will be given boundary condition and appropriate meshing process. Simulation of the solar dryer is done using Monte Carlo solar load model and two direction of sun beam was analyzed. The result for temperature distribution were taken from points, points cloud and volume rendering techniques. All of the result then analyzed and compared to each other to determine the best design for the solar dryer and the optimum operating condition. The simulation conclude that solar dryer with 45° reflector give the best temperature distribution when operating with the sun beam come directly from above and 45° from the side. The design of solar dryer with reflector on both side also yield better result compare to solar dryer with no reflector.